OS ANOS 1960 E A CULTURA DO CONSUMO SOB A PERSPECTIVA DA PUBLICIDADE VOLKSWAGEN - VALDÉS, MARCELO PATRICIO ALLENDES (2019)
This research seeks to analyze how advertising reflects the social, economic, political and cultural context in which it is inserted - and how this context interferes in the conditions of creation -, as well as to verify how the theories that explain the motivations of human consumption are present in the persuasive language of this publicity. The study was limited to the 1960s, in Brazil, by means of some announcements issued by Volkswagen during that decade. Thus, we chose a combination of bibliographical research and discourse analysis. In its final result, the work shows that advertising works directly, indirectly and symbolically messages recognizable to the reader, considering the cultural characteristics of a social group, through a marketing discourse where consumption transfers identity, differentiation and feeling of progress.